Task-specific resistance training adaptations in older adults: comparing traditional and functional exercise interventions - Pagan, Jason I.; Bradshaw, Bethany A.; Bejte, Brisilda; Hart, Jordan N.; Perez, Vanjeliz; Knowles, Kevan S.; Beausejour, Jonathan P.; Luzadder, Marc; Menger, Reed; Osorio, Carlos; Harmon, Kylie K.; Hanney, William J.; et al. (Frontiers in Aging, 2024)
Muscle strength declines ~3% per year after the age of 70. Resistance training guidelines for older adults are often based on free-weight and machine exercises, which may be inaccessible and lack carryover to activities of daily living. We tested the hypothesis that resistance training adaptations in older adults are task-specific. Thirty adults (8 males, 22 females; mean age = 71 years) were randomly assigned to participate in six weeks of supervised, high-intensity resistance training (twice per week) utilizing free-weight and machine exercises (traditional) versus functional activities that were overloaded with a weighted vest (functional). Participants were thoroughly familiarized with the exercises and testing prior to beginning the study. Major outcome measures included assessments of functional performance, five-repetition maximum strength, isometric knee extensor force, and quadriceps muscle size. Physical activity and nutrition were monitored. The study results demonstrate that the magnitude of improvement within a given outcome was largely dependent on group assignment, with greater improvements in gait speed and the timed-up-and-go in the functional group, but 2-3× greater five repetition maximum strength improvements for the trap bar deadlift, leg press, and leg extension following traditional resistance training. Both groups showed improvements in isometric knee extensor force and muscle size, suggesting that some aspects of the observed adaptations were generic, rather than specific. Overall, these novel findings suggest that, among older adults, 1) resistance training adaptations exhibit a high degree of task specificity and 2) significant improvements in functional outcomes can be achieved with the use of a weighted vest.